Chicken soup for the soul moms & sons : stories by mothers and sons, in appreciation of each other - Canfield, Jack 1944-; Hansen, Mark Victor; Newmark, Amy (Chicken Soup for the Soul Pub., 2008)
Collects over one hundred amusing and inspirational stories that celebrate the unique bond between mothers and their sons.